Chiral 1D perovskite microwire arrays for circularly polarized light detection. (March 2022) - Zhao, Yingjie; Li, Xinyi; Feng, Jiangang; Zhao, Jinjin; Guo, Yangwu; Yuan, Meng; Chen, Gaosong; Gao, Hanfei; Jiang, Lei; Wu, Yuchen
Highlights: Chiral 1D perovskite single-crystal microwire arrays are fabricated by using a capillary-bridge-manipulated method. By the synergy of the excellent crystallinity and sensitive circular-polarization absorption leads to high-performance CPL photodetectors, with a maximum anisotropy factor of 0.23, responsivity exceeding 26 mA W  −   1, and detectivity exceeding 2.2 × 10 11 jones. Microwire arrays present impressive environmental stability under ambient conditions for 30 days. Abstract: Detection of circularly polarized light (CPL) accelerates the development of various optical technologies, but the additional quarter-wave plate and linear polarizer are required for conventional polarized light detectors, resulting in tremendous difficulty in integration and miniaturization of the devices. Herein, we fabricate pure (010)-orientated chiral one-dimensional (1D) perovskite microwire arrays with high crystallinity, strict alignment, and homogeneous size by a capillary-bridge-manipulated method. By the synergy of the excellent crystallinity and pure crystallographic orientation, high-performance CPL photodetectors are fabricated, with a maximum anisotropy factor of 0.23, responsivity exceeding 26 mA W −1, and detectivity exceeding 2.2 × 10 11 Jones. Furthermore, the CPL photodetectors based on microwire arrays also exhibit impressive environmental stability under ambient conditions. Graphical abstract: Pure (010)-orientated chiral 1D perovskite single-crystalline microwire arrays are fabricated by the capillary-bridge-manipulated method. 1D perovskite microwire arrays exhibit impressive environmental stability under ambient conditions. Chiral microwire arrays integrate the excellent crystallinity and pure crystallographic orientation, yielding high-performance CPL photodetectors with a maximum anisotropy factor of 0.23, responsivity exceeding 26 mA W  −   1, and detectivity exceeding 2.2 × 10 11 Jones. Image, graphical abstract